Dioctophyme renale (Nematoda: Enoplida) in domestic dogs and cats in the extreme south of Brazil - Rappeti,Josaine Cristina da Silva (2017)
Abstract Dioctophyme renale is a zoonotic nematode that parasites the kidneys of wild and domestic carnivores, and it has been reported frequently in Brazil. The aim here was to register the number of cases of dogs and cats diagnosed with dioctophymosis by necropsy (1981 to 2014) and ultrasound examination (2010 to 2015) in Pelotas-RS. In this context, a survey was conducted on dioctophymosis cases diagnosed at the Veterinary Pathology Laboratory (LPV) and Veterinary Clinical Hospital (HCV) of the Federal University of Pelotas (UFPel), and at a specialist veterinary imaging diagnostics clinic. In total, 95 cases were registered. The high series of the disease in dogs can be related to the presence of a large number of stray and semi-domestic dogs in the city, and also due to the ingestion of intermediate hosts of D. renale parasitized with the infective larvae. Thus, it can be concluded that Pelotas is a city with favorable conditions for the occurrence of dioctophymosis with high rate of disease in recent years.